DETERMINANTS OF FINANCIAL PERFORMANCE AND THEIR IMPLICATIONS FOR COMPANY VALUES: Empirical Study of Automotive Sub-Sector and Registered Components on the Indonesia Stock Exchange - Siahaan, Matdio; Gursida, Hari; Sasongko, Hendro (Yayasan Education and Social Center, 2024)
The company aims to improve the welfare of shareholders by obtaining high company value as measured through various aspects including the company's stock price which can reflect the overall investor assessment of each equity owned in the Automotive and Component companies listed on the Indonesia Stock Exchange in 2019-2023. The data in this study are secondary data obtained through the company's annual financial reports which will be studied during the 2019-2023 period. This study aims to determine the effect of capital structure, company size, managerial ownership and institutional ownership on company value as proxied by price to book value (PBV). The sample selection method uses the purposive sampling methodnamely the selection of sample members based on certain criteria, with the number of companies sampled in this study as many as 12 companies, namely automotive and component sub-sector companies with an observation period of five years, so that the total observation data is 60. The research method used is a quantitative research method. The regression results show that for 2019-2023, Capital Structure (0.787), Managerial Ownership (-0; 364) and Institutional Ownership (0.461) have a significant effect on Financial Performance (0,995) while Company Size (0.015) does not have a significant effect on company value